(untitled) (Bulletin of Taras Shevchenko National University of Kyiv. Social Work, 2020)
The author reveals the peculiarities of formation of pro-social behavior of adolescents that draw attention of scientists-practitioners and society, bearing in mind the difficult socio-economic, political and military situation in Ukraine. In the article, the authentic determination of ’pro- social behavior’ is presented as a complex and social psychological phenomenon that develops in the process of a personality formation. The essence and mechanisms of organization of educational process subjects’ interaction are revealed; results of experimental activity (criteria and indices of pro-social behavior of vulnerable adolescents are determined: the problematic areas of activity are defined: teenagers’ inability of proper conduct in conflict situations, of negative answers to a risky offer, insufficient motivation to pro-social actions, limited pro-social behavior manifestations in everyday life; the rating of game technology application in the educational process of educational institutions, and successful practical introductions of game technologies of teenagers’prosocial behavior formation due its essential features: personal orientation, dialogical orientation, two-centered relations between participants, are given.